Estudo tectono-sedimentar da Bacia de Jaibaras, na região entre as cidades de Pacujá e Jaibaras, noroeste do estado do Ceará - QUADROS, Marcos Luiz do Espírito Santo (Universidade Federal do Pará, 2017)
Studies carried out in southwestern portion of the Jaibaras Basin in the area of the 300 km², situated between the Pacujá and Jaibaras towns, northwest region of Ceará State, including geological mapping in 1:25,000 scale, faciologic, petrographic and structural analysis of the Pacujá and Aprazível formations, allowed a better visualization of spatial distribution of these units, as well as the characterization of their depositional environment, structural pattern and, at last to take considerations about the tectono-sedimentary evolution of the Jaibaras Basin. The Pacujá Formation is characterized by a folded and faulted volcanosedimentary sequence without fossils, made of rhythmic interlayers of fine arkosian sandstones to siltistones with pelites, occurring in tabular decimeter thick beds, laterally continuous, showing abrupt base and upward gradation to siltistones. The sandstones could be massive or stratified, showing planar lamination, micro-hummocky cross lamination, climbing wave -ripple cross lamination, locally parting lineation and convolute lamination. On the top of the sandstone beds occur symetrical and assymetrical wavy-ripples. Pelites show planar lamination and mudcracks. Interlayered with Pacujá Formation sediments occur volcanic and subvolcanic rocks (basalts, andesites, dacites and ryolites), at the form sills, dikes and flows, associated with volcaniclastic rocks, included on the Parapuí Suite. The environment of the Pacujá Formation was characterized as lacustrine with volcanism associated, subjected to storm-wave action, proved by the occurrence of microhummocky cross lamination.The rhythmics interlayering of sandstones and pelites characterizes tempestites cycles, usually incomplete. However, marine environment must be assoc iated, but unfortunately the field datas is insufficient to define this environments. In the Jaibaras Basin setting, Pacujá Formation represents the first deposicional pulse that extend from Neoproterozoic era to Cambrian period. This sedimentation occurred in an area wider than Jaibaras Basin out of their present boundaries. The Pacujá Formation shows a complex fold pattern, that resulted from superimposed folding, with geometric shapes similar to type 1 interference pattern - “domes and basins”, and kinks folds. This folding could be related to transpression in ductile -brittle regime, linked to the northest-southwest sinistral strike -slip system in the Eopaleozoic era, that caused a weak inversion of the Jaibaras Basin. The Aprazível Formation comprises a thin sedimentary sequence, faulted and tilted to southeastern on the whole, unconformably covering the Pacujá Formation. It is made of polymitic conglomerates, with clast-supported and matrix -supported framework, massive or stratified, with volcanic, gneiss, granite, rocks calcissilicatic, quartz, amphibolite, rhyolite, marble, mylonite, siltistone and sandstone clasts, varying in size from granules to boulders. The matrix is coarse to very coarse sandy arkosean, locally microconglomeratic. To a lesser proportion, occurs medium to very coarse grained arkosean sandstones, locally stratified, and intercalations of laterally continuos beds of arkosean sandstones and laminated pelites with mudcracks in surfaces of the beds. These sandstones show planar lamination, climbing-ripple cross lamination, and locally trough cross-bedding and convolute lamination. In the surface of sandstone beds, there are, occasionally, symetrical and assymetrical wave-ripples. The depositional environment of the Aprazível Formation was characterized as alluvial fan/plain, dominated by debris-flows and stream-flows, prograding distally over small lacustrine bodies. The tilting of the Aprazível Formation beds to southeastern, is a results from rotation of blocks, due to an extensional axis in the northwest-southeast direction, acting in Ordovician period, that controlled the deposition of Aprazível Formation in the area between Sobral-Pedro II and Café -Ipueiras shear zones. The Aprazível Formation represents the second and last depositional pulse that occurred in the Jaibaras Basin in the Ordovician period, in a more restrict depositional area, controled by Sobral-Pedro II e Café-Ipueiras shear zones. Its deposition occurred in a time interval between the post-Pacujá sequence and Meruoca Suite Granites, and pre-Serra Grande Group sequence of the Parnaiba Basin.